Implementation of Simple Additive Weighting on Decision Support System for Accoustic Guitar with Web-Based (Study Case: Chaniago Sport) - Frans Imanuel; Fenina Adline Twince Tobing (Universitas Multimedia Nusantara, 2022)
The acoustic guitar is one of the most popular musical instruments because music itself is a universal language that everyone can understand. Acoustic guitars are available in many choices such as wood types, brands, prices, and many sizes. Many people who want to buy a guitar are often confused when they have to choose an acoustic guitar that suits their needs, this happens because there are many aspects of an acoustic guitar that must be considered as already mentioned. The demands of work and the busyness of today’s society This makes many people unable to choose and see the acoustic guitar according to their needs in music stores. Therefore, this system was created as an acoustic guitar recommendation system, so that people can choose an acoustic guitar that suits their needs and buy an acoustic guitar online based on people’s preferences. The recommendations given by this system are obtained from calculations using the simple additive weighting method or known as the weighted addition method. This simple additive weighting method has been tested in this study and can be implemented correctly and as needed. End-user satisfaction is also obtained using the end-user computing satisfaction (EUCS) method so that the recommendation system that has been successfully built can be said to be very good for users in providing acoustic guitar recommendations.